Analysis of Supervision and Audit Strategy in Improving Compliance of BPJS Employment Participant Companies - Sirait, Wira Junjungan; Mujahid, Mujahid; Syuthi, Nurmadhani Fitri (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This study explores the effectiveness of supervision and inspection strategies employed by BPJS Ketenagakerjaan to enhance compliance among participant companies. Through a descriptive approach, interviews were conducted with internal (BPJS inspectors) and external (company representatives) stakeholders. The findings reveal that strategies focusing on Law Enforcement (sanction enforcement, compliance collaboration, and supervision enhancement) and Collection (digitalization and collaboration) have been well-implemented and understood across different organizational levels. Key factors influencing strategy success include effective communication, adequate resources, appropriate attitudes, and streamlined bureaucracy. Insights from both BPJS inspectors and company respondents underscore the significance of these strategies in fostering compliance with BPJS Ketenagakerjaan programs. This research contributes to understanding the pivotal role of supervision and inspection in regulatory compliance within social security frameworks.